Urban studies in the context of theories of visual practices - A. M. Tormakhova, (Ukrainian Cultural Studies, 2017)
One of the leading trends in contemporary cultural studies is the appeal to the field of visual. The purpose of the article is to investigate the range of problems associated with the existence, functioning of various visual practices in the urban space and the disclosure of the specifics of communication carried out through their intermediation. In urban space, there are many forms, such as monumental architecture, urban sculpture, outdoor illumination, landscape art, street art, graffiti and others. These artifacts are the subject of cultural research within different disciplines - aesthetics, cultural studies, design, and art. It may be noted that in recent decades, significant development gets such a direction as Urban Studies, in which the focus of research serves the city. The methodology of the study includes an appeal to an interdisciplinary approach that relies on the achievements of practical cultural studies, Urban studies, and aesthetics theory by Ukrainian and Western authors. Scientific novelty consists in analyzing the connection of actual visual practices presented in the urban space and forming of Internet activity, which facilitates the mutual influence of these spheres one on another. The author noted that urban space is gradually becoming not only interactive, but also fully assuming the characteristics of WEB 2.0, which means active rethinking and transforming the environment, urban residents involvement in decision-making that becomes a norm of everyday life. City is a kind of text that reflects changing tastes, political and economic factors in visual form. Town and city public spaces play an important role in shaping the interaction within society. One of the pressing problems of practical cultural studies in general and urban areas in particular, should be integrated into organization of the urban environment and design the image of the city. The practical significance lies in the fact that the results of the research can be used in developing the urban sphere in particular and in actualizing the issue of organizing the urban environment and constructing the image of the city.
Keywords: urban space, visual practices, communication, Urban studies, metamodernizm